The Existence Of Teachers Of Uptd Sdn 1 Samalanga In Forming Anti-Bullying Character Of Students - Muhibuddin, Muhibuddin; Dhiauddin, Dhiauddin; Saifuddin, Saifuddin (PT. Anagata Sembagi Education, 2025)
Bullying behavior in schools remains an issue that hinders the development of students' positive character. This study aims to identify the role of teachers, learning strategies, and supporting as well as inhibiting factors in the formation of anti-Bullying character at UPTD SD Negeri 1 Samalanga. The findings reveal that (1) teachers play a strategic role as role models in instilling values of empathy, tolerance, and respect for diversity through integration in the curriculum and school programs. Open communication between teachers, students, and parents is also a key to success. (2) Learning strategies involve interactive approaches, such as group discussions, role-playing, and social activities that strengthen solidarity. Collaboration with parents through seminars and regular meetings reinforces the synergy between school and family. The study concludes that UPTD SD Negeri 1 Samalanga has developed the